Formation of a transition V-rich structure during the α' to α + β phase transformation process in additively manufactured Ti-6Al-4 V. (15th August 2022) - Wang, H.; Chao, Q.; Chen, H.S.; Chen, Z.B.; Primig, S.; Xu, W.; Ringer, S.P.; Liao, X.Z.
Abstract: Ti-6Al-4V parts fabricated by laser powder-bed fusion (L-PBF) additive manufacturing often suffer from poor ductility and low toughness due to the predominance of the acicular α' martensitic phase in their microstructures. This challenge can be overcome by manipulation of the L-PBF thermal history to introduce an α'→ α+β decomposition, resulting in a fine lamellar α+β structure with a combination of excellent strength and ductility. Understanding the details of the α'→ α+β phase transformation process is critical for fabricating titanium alloys with excellent mechanical properties. Through a systematic electron microscopy characterisation of the microstructural evolution of a Ti-6Al-4V alloy fabricated by L-PBF, here we reveal that the α'→ α+β phase transformation occurs in two steps: α'→ α+ αHME (high in Moeq ) and αHME  → β, in which αHME is a newly discovered non-equilibrium structure with a hexagonal close-packed structure and with a composition close to that of the β phase. Graphical abstract: Image, graphical abstract